Reasons and habits that affect the practice of physical activity in high school students - Eddy Jacobb Tolano Fierros (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The practice of physical activity presumes numerous benefits by virtue of the way in which it is carried out, in addition to the purposes that are desired to achieve, based on the objectives to know and analyze, the reasons and habits with respect to the practice of physical activity in third grade students of a school in Obregon City, Sonora Mexico. The design of this research is mixed. A convenience sampling was used, which was conformed by 96 students of the third grade of high school; all of them with 14 years of age. The questionnaire "Yesterday Activity Cheklist" was used, adapted for young people from 10 to 16 years old, as well as documentary review and observation. Among the results obtained, the frequency with which girls perform physical activity is lower when compared to boys, which is low in both cases. The determining reason why they practice physical activity is because they like it and have fun, and an alarming fact is that part of the population does not practice physical activity due to lack of time and the greater percentage predominates in boys. Based on all these results, the aim is for teachers and parents to promote physical activity with their students and children in order to improve their quality of life.